2012
DOI: 10.6061/clinics/2012(10)05
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy reactions: coinfections as a possible risk factor

Abstract: OBJECTIVE:This study aimed to determine the frequency of coinfections in leprosy patients and whether there is a relationship between the presence of coinfections and the development of leprosy reactional episodes.METHOD:A cross-sectional study based on an analysis of the medical records of the patients who were treated at the Leprosy Clinics of the Ribeirão Preto Medical School, University of São Paulo, was conducted from 2000 to 2010. Information was recorded regarding the age, sex, clinical status, WHO clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 13 publications
4
59
0
13
Order By: Relevance
“…We found that ENL was the most prevalent reaction type, especially in MB patients with any coinfection. We verified that oral infections, including periodontal diseases and dental abscess, were the most prevalent coinfections, followed by urinary tract infection, sinusopathy, and viral hepatitis (Motta et al , , ). These findings suggest that the presence of coinfections may be involved in the development and maintenance of leprosy reactional episodes and raise the need to screen these patients for chronic systemic and local infections.…”
Section: Reactional Episodes and Oral Infectionssupporting
confidence: 60%
See 1 more Smart Citation
“…We found that ENL was the most prevalent reaction type, especially in MB patients with any coinfection. We verified that oral infections, including periodontal diseases and dental abscess, were the most prevalent coinfections, followed by urinary tract infection, sinusopathy, and viral hepatitis (Motta et al , , ). These findings suggest that the presence of coinfections may be involved in the development and maintenance of leprosy reactional episodes and raise the need to screen these patients for chronic systemic and local infections.…”
Section: Reactional Episodes and Oral Infectionssupporting
confidence: 60%
“…The relationship between these reactional episodes and infectious process has been investigated. We studied the role of coexisting factors that could be related to exacerbation of M. leprae infection (Motta et al , ). First, we determined the frequency of leprosy reactional episodes and coinfections in LPs to evaluate whether there was a relationship between these conditions.…”
Section: Reactional Episodes and Oral Infectionsmentioning
confidence: 99%
“…2,13 Namun ada juga penelitian yang berkesimpulan sebaliknya, bahwa kusta lebih banyak pada laki-laki. 8,14 Beberapa kebiasaan menunjukkan adanya keterbatasan perempuan dalam pencarian pengobatan dan keluhan kusta terkait dengan stigma dalam masyarakat, sehingga jumlah penderita kusta perempuan yang tercatat lebih sedikit dan seringkali ditemukan sudah dalam keadaan cacat. 2,12,13 Pada penelitian ini didapatkan dua kelompok subyek berdasarkan jenis kusta, yaitu PB dan MB.…”
Section: Pendahuluanunclassified
“…Hal yang sama juga diungkapkan oleh beberapa hasil penelitian di dunia. 6,8,14,15 Reaksi kusta merupakan reaksi hipersensitivitas, sehingga sangat dipengaruhi oleh respon imun dan status imunitas seseorang. 2,16 Sebuah studi menunjukkan adanya peningkatan aktifitas sel T helper 17 pada kelompok orang yang mengalami reaksi kusta, dimana sel ini memegang peranan penting dalam proses autoimun dan reaksi inflamasi.…”
Section: Pendahuluanunclassified
“…Cytokine measurement during the reactional episodes has been reported in many studies, especially T cell biomarkers analyzed in plasma, serum, skin lesions and saliva [3][4][5][6][7][8][9][10] , demonstrating their potential to play a significant role in the classification, prognosis and evolution of leprosy. We have been studying the relationship between these episodes and infectious processes such as chronic oral infections 11 . Since oral infections can induce over-stimulation of the host immune system through the release of inflammatory peptides 12,13 , it is reasonable to consider the possibility that these infectious processes act as an inducing and exacerbating or maintaining factor of leprosy reactions.…”
Section: Introductionmentioning
confidence: 99%